The diagnosis and formation of professional fitness from the point of view of the instrumental theory of purposefulness - Kregždė, S. (Psichologija, 1988)
The paper deals with the instrumental theory of vocational purposefulness as the best approach to the diagnosis and formation of the basic motivational component of professional fitness. The sequel of research conducted adhering to this theory (J. Čebelis, V. Rimkevičienė, L. Kutkienė, J. Navaitienė, R. Kabašinskienė, A. Kregždė, I. Yakimova) is presented.